2022
DOI: 10.1080/1553118x.2021.2023544
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Internal Communication in Start-ups: State of Research and Practical Approaches

Abstract: The main objective of this paper is to analyze how strategic communication promotes corporate productivity in the 21st century. For this reason, a bibliographic review of the main concepts related to this topic in literature from research articles, scientific journals and books is carried out.As a complement to the study, a review of similar positions and an exploration of the main variables around the subject were carried out; likewise, the theoretical framework is made up of aspects such as strategic communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…A fourth group of 12 articles (13.2%) focused primarily on specific contexts of increased interest to business communication scholars: after-hours communication (Kim & Chon, 2022), startups (Wolf et al, 2022), change management (Dulek, 2015), and distributed or virtual organizations (Aritz et al, 2018; Berg, 2012; Lockwood & Song, 2020; Newman et al, 2020; Smith et al, 2018; Viererbl et al, 2022). Three articles reviewed emerging practices across business organizations more generally (Coffelt & Smith, 2020; Cyphert et al, 2019; Waldeck et al, 2012).…”
Section: An Analysis Of the Rhetorical Evolution In The Business Comm...mentioning
confidence: 99%
“…A fourth group of 12 articles (13.2%) focused primarily on specific contexts of increased interest to business communication scholars: after-hours communication (Kim & Chon, 2022), startups (Wolf et al, 2022), change management (Dulek, 2015), and distributed or virtual organizations (Aritz et al, 2018; Berg, 2012; Lockwood & Song, 2020; Newman et al, 2020; Smith et al, 2018; Viererbl et al, 2022). Three articles reviewed emerging practices across business organizations more generally (Coffelt & Smith, 2020; Cyphert et al, 2019; Waldeck et al, 2012).…”
Section: An Analysis Of the Rhetorical Evolution In The Business Comm...mentioning
confidence: 99%
“…This idea is related to 'work meaningfulness' in leadership literature (Kipfelsberger et al, 2022). Wolf et al (2022) reported, based on 12 interviews, that explaining why is important for activity coordination in internal communications in IT-intensive start-up companies. Smart (2018) also recommended Sinek's (2011) advice when implementing agility in DevOps environments.…”
Section: Always Explain Whymentioning
confidence: 99%
“…Es así que la academia ha ido trabajando estos años en la formación de un cuerpo conceptual de la comunicación organizacional interna, surgiendo nuevas teorías y enfoques. Entre las investigaciones que destacan en las principales bases de datos se encuentran las de Estados Unidos y Europa (Tkalac y Pološki, 2017;Ihm y Kim, 2021;Wolf, Godulla, Beck y Neubert, 2022;Yue, Men y Ferguson, 2021; las cuales tienen ciertas similitudes entre ellas en cuanto a aspectos como enfoque y metodología de investigación.…”
Section: Introductionunclassified